Maternal hepatitis C prevalence and trends by county, US: 2016–2020. Issue 2 (13th November 2022) - Ahrens, Katherine A.; Rossen, Lauren M.; Burgess, Amanda R.; Palmsten, Kristin; Ziller, Erika C.
Abstract: Background: Trends in the prevalence of hepatitis C virus (HCV) infection among women delivering live births may differ in rural vs. urban areas of the United States, but estimation of trends based on observed counts may lead to unstable estimates in rural counties due to small numbers. Objectives: The objective of the study was to use small area estimation methods to provide updated county‐level prevalence estimates and, for the first time, trends in maternal HCV infection among live births by county‐level rurality. Methods: Cross‐sectional natality data from 2016 to 2020 were used to estimate maternal hepatitis C prevalence using hierarchical Bayesian models with spatiotemporal random effects to produce annual county‐level estimates of maternal HCV infection and trends over time. Models included a 6‐level rural–urban county classification, year, maternal characteristics and county‐specific covariates. Data were analysed in 2022. Results: There were 90, 764/18, 905, 314 live births (4.8 per 1000) with HCV infection reported on the birth certificate. Hepatitis C prevalence was higher among rural counties as compared to urban counties. Rural counties had the largest annual increases in maternal hepatitis C prevalence (per 1000 births) from 2016 to 2020 (micropolitan: 0.39; noncore: 0.40), with smaller increases among less densely populated urban counties (medium metro: 0.28; small metro: 0.28) and urban counties (large central metro:0.11; large fringe metro: 0.14). Conclusions: The prevalence of maternal HCV infection was the highest in rural counties, and rural counties saw the greatest average prevalence increase during 2016–2020. County‐level data can help in monitoring rural–urban trends in maternal HCV infection to reduce geographic disparities.